Generator Pulsa Arus - Mak Sioe Tho (Journal of Mathematical and Fundamental Sciences, 1965)
Ichtisar. Dalam penjelidikan mengenai karakteristik suatu arrester, selain mengetahui karakteristik tembus terhadap tegangan pulsa djuga perlu diselidiki sifat2 tahanan non linearnja (lazim dipergunakan Si C) terhadap pulsa arus menentukan tegangan tinggalnja (Rest spanning). Untuk kepentingan ini dipergunakan pulsa arus 5 x 10 Î¼ sec ataupun 10 x 20 Î¼ sec. Disini akan dibahas mengenai parameter2 rangkaian dan faktor2 jang penting diperhatikan dalam perentjanaan suatu generator pulsa arus. Abstract. In order to obtain the performance characteristic of an arrester, besides knowing the breakdown voltage of its gaps it is also necessary to know the behaviour of the non linear value element (usually Si C) with respect to current surges to get a picture of its rest voltage. For this purpose  5 x 10 Î¼ sec or 10 x 20 Î¼ sec current surges are used. The circuit parameters, and some important factors concerning the design of a current surges generator are discussed here.